THE SECOND LINK IN THE CHAIN OF SURVIVAL IN OUT-OF-HOSPITAL CARDIAC ARREST - Jakšić, Stefan (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction: Early recognition and seeking help, early CPR, early defibrillation, and post-resuscitation treatment make up four links in the survival chain for sudden cardiac arrest.The Aim: To determine the representation of BLS by eyewitnesses in patients in out of hospital cardiac arrest until the arrival of the ambulance, telephone assisted CPR, and whether the measures taken, affect the rate of establishment of ROSC.Material and Methods: The study is retrospective and observational.Results: 148 patients were enrolled in the study. In the group of patients who survived cardiac arrest in the presence of ambulance, stand out as statistically significant in relation to the group of patients who did not survive.Conclusion: Implementation of protocol for telephone-assisted CPR in dispatch centers would increase the number of cases in which a layman would undertake CPR measures prior to the arrival of the team.
Keywords: sudden cardiac arrest; CPR; ROSC